Innovation System in the Sidoarjo People's Service System (SIPRAJA) in Sidoarjo Regency - Jiana Walida; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2022)
The Sidoarjo People’s Service System Innovation (SIPRAJA) is an innovation of the Sidoarjo Regency/City government. This study aims to analyze and describe the obstacles that occur in innovation in the Sidoarjo people service system (SIPRAJA) in Sidokerto Village, Buduran District, Sidoarjo Regency, namely yhe conditionof the community that is still difficult to adapt or keep up with increasingly shophisticated times and the internet network is lacking stable. This research uses systems innovation theory. The research method uses a qualitative descriptive approach using data collection techniques in the form of interviews, documentation, and observation. The results of this study indicate that the innovation of the Sidoarjo People’s Service System (SIPRAJA) in Sidokerto Village, Buduran District, Sidoarjo regency, nemly focusing on the innovation system providing convenience in mail management services effectively and efficiently.